Health care workers' risk perceptions and willingness to report for work during an influenza pandemic - Georges Dionne; Denise Desjardins; Martin Lebeau; Stéphane Messier; André Dascal (Risks, 2018)
The ability and willingness of health care workers to report for work during a pandemic are essential to pandemic response. The main contribution of this article is to examine the relationship between risk perception of personal and work activities and willingness to report for work during an influenza pandemic. Data were collected through a quantitative Web-based survey sent to health care workers on the island of Montreal. Respondents were asked about their perception of various risks to obtain index measures of risk perception. A multinomial logit model was applied for the probability estimations, and a factor analysis was conducted to compute risk perception indexes (scores). Risk perception associated with personal and work activities is a significant predictor of intended presence at work during an influenza pandemic. This means that correcting perceptual biases should be a public policy concern. These results have not been previously reported in the literature. Many organizational variables are also significant.
Keywords: D80; I11; I18; 330; influenza pandemic; pandemic preparedness; risk perception; reporting for work; health policy; personal and work activities; principal component analysis